Immune Modulation by Volatile Anesthetics - Stollings, Lindsay M.; Jia, Li-Jie; Tang, Pei; Dou, Huanyu; Lu, Binfeng; Xu, Yan (Anesthesiology (Philadelphia), 2016)
Volatile general anesthetics continue to be an important part of clinical anesthesia worldwide. The impact of volatile anesthetics on the immune system has been investigated at both mechanistic and clinical levels, but previous studies have returned conflicting findings due to varied protocols, experimental environments, and subject species. While many of these studies have focused on the immunosuppressive effects of volatile anesthetics, compelling evidence also exists for immunoactivation. Depending on the clinical conditions, immunosuppression and activation due to volatile anesthetics can be either detrimental or beneficial. This review provides a balanced perspective on the anesthetic modulation of innate and adaptive immune responses as well as indirect effectors of immunity. Potential mechanisms of immunomodulation by volatile anesthetics are also discussed. A clearer understanding of these issues will pave the way for clinical guidelines that better account for the impact of volatile anesthetics on the immune system, with the ultimate goal of improving perioperative management.